2010
DOI: 10.1158/1541-7786.mcr-09-0497
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Knockdown of SEPT9_v1 Inhibits Tumor Growth and Angiogenesis of Human Prostate Cancer Cells Concomitant with Disruption of Hypoxia-Inducible Factor-1 Pathway

Abstract: Hypoxia-inducible factor-1 (HIF-1) is a key transcription factor in the hypoxic response pathway. We recently identified a novel interaction between HIF-1α and the mammalian septin family member, septin 9 protein, isoform 1 (SEPT9_i1), a protein product of septin 9 transcript variant 1 (SEPT9_v1). Septins are a highly conserved family of GTP-binding cytoskeletal proteins that are implicated in multiple cellular functions, including oncogenesis. SEPT9_i1 binds and stabilizes HIF-1α protein and stimulates HIF-1 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 33 publications
6
35
0
Order By: Relevance
“…The interaction of overexpressed SEPT9_v1 with HIF-1a in prostate cancer results in increased cell proliferation and tumor angiogenesis, whereas the knockdown of SEPT9_v1 is associated with an increase in HIF-1a degradation, a decrease in HIF-1 transcriptional activity, cell proliferation and angiogenesis. Collectively, these findings suggest and support a significant role of this interaction in prostate tumor progression (Amir et al, 2006(Amir et al, , 2010.…”
Section: Hormonally Regulated Carcinomas and Septins (Prostate Ovarisupporting
confidence: 63%
See 2 more Smart Citations
“…The interaction of overexpressed SEPT9_v1 with HIF-1a in prostate cancer results in increased cell proliferation and tumor angiogenesis, whereas the knockdown of SEPT9_v1 is associated with an increase in HIF-1a degradation, a decrease in HIF-1 transcriptional activity, cell proliferation and angiogenesis. Collectively, these findings suggest and support a significant role of this interaction in prostate tumor progression (Amir et al, 2006(Amir et al, , 2010.…”
Section: Hormonally Regulated Carcinomas and Septins (Prostate Ovarisupporting
confidence: 63%
“…The outcome of these rearrangements is the loss of the variable region at the N-terminus of the protein that characterizes SEPT9 isoforms _v1 and _v2. Interestingly, although the function of SEPT9 isoform variants in tumorigenesis remains largely unknown, the evidence supporting an oncogenic role for _v1 seems quite compelling (Gonzalez et al, 2007;Amir et al, 2010). It is intriguing that the MLL fusion proteins lose the genomic region responsible for the genetic variation of the SEPT9_v1 isoform, which seems to be required for its oncogenic properties in solid tumors.…”
Section: The Role Of Septins In Hematological Malignanciesmentioning
confidence: 99%
See 1 more Smart Citation
“…1G). Of note, long SEPT9 isoforms have been shown to be upregulated in various tumors and cancer cell lines (Amir et al, 2010;Connolly et al, 2014;Connolly et al, 2011b;Stanbery et al, 2010). It remains to be determined whether and to what extent their interaction with CIN85 might contribute to cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that septin 9 promotes angiogenesis and facilitate tumor growth in the hetero-transplant model [9]. In contrast, breast cancer-related studies have indicated distinct cellular functions and suggested a tumor-suppressor role [10].…”
Section: Introductionmentioning
confidence: 99%